Cu–Immobilized Mesoporous Silica Nanoparticles [Cu2+@MSNs‐(CO2−)2] as an Efficient Nanocatalyst for One‐Pot Synthesis of Pyrazolopyranopyrimidines in Water. Issue 30 (23rd October 2017) - Nasresfahani, Zahra; Kassaee, Mohammad Zaman
Abstract: Abstract Cu 2+ @MSNs‐(CO2 − )2 has been prepared and characterized by using small angle powder X‐ray diffraction (XRD), Nitrogen adsorption–desorption analysis, Scanning electron microscopy (SEM), Transmission electron microscopy (TEM), Energy dispersive X‐ray (EDX), Thermal analyses (TGA‐DTA) and FT‐IR studies. A facile one‐pot, four‐component condensation reaction of ethyl acetoacetate, hydrazine hydrate, aromatic aldehydes, and barbituric acid for synthesis of pyrazolopyranopyrimidines is efficiently catalyzed over Cu 2+ @MSNs‐(CO2 − )2 in water. This catalyst is easily recovered from the reaction mixture and reused several times without any loss in catalytic activity. Abstract : Preparation and catalytic activity of Cu 2+ @MSNs‐(CO2 − )2 in four‐component condensation reaction of ethyl acetoacetate, hydrazine hydrate, aromatic aldehydes, and barbituric acid for synthesis of pyrazolopyranopyrimidines.